A study of socio-demographic and diagnostic profile of patients attending the psychiatric out-patient department of Nobel Medical College Biratnagar - Koirala, Naba Raj; Yadav, Rajesh; Das, Ajay Kumar; Poudel, Jwalanta; Bhagat, Santosh Kumar (Journal of Nobel Medical College, 2012)
Study on prevalence of psychiatric disorders in Eastern part of Nepal, is relatively understudied subject in Nepal. The present study is undertaken with the aim to study the socio-demographic characteristics and diagnostic profile of patients attending the psychiatry OPD of Nobel Medical College, that provides both outpatient and inpatient services to psychiatric patients residing in eastern part of Nepal and nearby Indian villages. It was a retrospective study where all consecutive patients attending the Psychiatry OPD from 1st May 2011 to 30th April 2012 and fulfilling the diagnostic criteria for Category F of ICD-101 were included in the study. Amongst the total number of 637 patients, cases with Epilepsy (N=44), Headache (N=53), other medical disorders (N=13) and incomplete case record (N=17) were excluded, and the final sample size was comprised of 510 cases (males=214 and females=296). Maximum numbers of patients were in the age-group 16-40 years (N=238, 47%) and were married (N=416, 79.04%). Most of the patients suffered from Neurotic stress-related and somatoform disorders (N=214, 41.96%), followed by Mood (N=168, 32.94%) and Schizophrenia, schizotypal and related disorders (N=56, 10.98%).DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7299 Journal of Nobel Medical College (2012), Vol.1 No.2 p.45-49